PRESSURE PAIN EVALUATION IN KNEES OF RATS SUBMITTED TO RESISTANCE EXERCISE (Fiep Bulletin - online, 2011)
Joint pain occurs in response to tissue aggression. The use of NSAIDS, steroids and analgesics has been associated with efficacy in the joint pain treatment, however, the side effects of such therapies, limit its use. Thus physical modalities earn their place in the treatment of such injuries, such as TENS, low-power laser and exercise, which presents some disagreement in the literature with respect to its real benefit. So the goal of this study was to evaluate the use of resistive exercise on joint pain in the knees of rats subjected to injection of formalin 5%. We used 14 male Wistar rats, they were divided into two groups: Placebo Group and Jump Group. To induce nociception was injected into the right knee medial tibio-femoral space, 50 μL of 5% formalin solution. Pain was assessed with use of Digital Analgesymeter, measuring the pressure required to produce limb withdrawal, either by stimulation of the plantar surface of the animal right paw, as in the lateral right knee. The evaluations were performed before induction of pain, after 15 and 45 minutes and finally after 2 hours of induction. For JG the exercise consisted of four sets of 5 jumps in water, loaded with 50% of body weight. In both forms of assessment used, for PG decreased the withdrawal threshold, no return to baseline, or increase with respect to the second evaluation. JG also decreased the pain threshold in the 2nd assessment, but after the exercise, the thresholds returned to pre-injury, with a significant increase when compared with the pre-exercise. We conclude that the pain produced by 5% formalin was attenuated with resistance exercise.
Keywords: exercise; pain measurement; hydrotherapy